Asymmetric Nerve Enlargement: A Characteristic of Leprosy Neuropathy Demonstrated by Ultrasonography. - Helena Barbosa Lugão; Marcello Henrique Nogueira-Barbosa; Wilson Marques; Norma Tiraboschi Foss; Marco Andrey Cipriani Frade (PLoS Neglected Tropical Diseases, 2015)
BACKGROUND:Neurological involvement occurs throughout the leprosy clinical spectrum and is responsible for the most feared consequences of the disease. Ultrasonography (US) provides objective measurements of nerve thickening and asymmetry. We examined leprosy patients before beginning multi-drug therapy aiming to describe differences in US measurements between classification groups and between patients with and without reactions. METHODOLOGY/PRINCIPAL FINDINGS:Eleven paucibacillary (PB) and 85 multibacillary (MB) patients underwent nerve US. Twenty-seven patients had leprosy reactions (type 1, type 2 and/or acute neuritis) prior to US. The ulnar (at the cubital tunnel-Ut-and proximal to the tunnel-Upt), median (M) and common fibular (CF) nerves were scanned to measure cross-sectional areas (CSAs) in mm2 and to calculate the asymmetry indexes ΔCSA (absolute difference between right and left CSAs) and ΔUtpt (absolute difference between Upt and Ut CSAs). MB patients showed greater (p<0.05) CSAs than PB at Ut (13.88±11.4/9.53±6.14) and M (10.41±5.4/6.36±0.84). ΔCSAs and ΔUtpt were similar between PB and MB. The CSAs, ΔCSAs and ΔUtpt were similar between PB patients with reactions compared to PB patients without reactions. MB patients with reactions showed significantly greater CSAs (Upt, Ut and M), ΔCSAs (Upt and Ut) and ΔUtpt compared to MB patients without reactions. PB and MB showed similar frequencies of abnormal US measurements. Patients with reactions had higher frequency of nerve thickening and similar frequency of asymmetry to those without reactions. CONCLUSIONS/SIGNIFICANCE:This is the first study to investigate differences in nerve involvement among leprosy classification groups using US before treatment. The magnitude of thickening was greater in MB and in patients with reactions. Asymmetry indexes were greater in patients with reactions and did not significantly differ between PB and MB, demonstrating that asymmetry is a characteristic of leprosy neuropathy regardless of its classification.